Study on Static Testing for Composite Wing of a Two-seater Seaplane - Sinchai Chinvorarat; Boonchai Watjatrakulq; Pongsak Nimdum; Teerawat Sangpet; Tosaporn Soontornpasatch; Pumyos Vallikul (Advanced Aspects of Engineering Research Vol. 8, 2021)
The paper studied the strength and deformation characteristics of a composite wing of a two-seater seaplane to get the certificate of airworthiness, which static testing is indispensable. The primary wing structure component includes upper and lower skins, leading edge, trailing edge, a root rib, and main spar. The main purpose of static testing is to examine the bending strength of the wing. The deformation of the wing and measured strain data were collected by a computer. The testing results show good agreement with the FE analysis results, and the bending strength of the wing is strong enough to support the limit loads (the maximum loads to the expected in-service) without detrimental and permanent deformation and without failure for at least 3s under the ultimate loads (limit loads multiplied by prescribed factors of safety), which meets the requirement of ASTM F2245-16c (Standard Specification for Design and Performance of a Light Sport Airplane).